1996
DOI: 10.1029/95rs03258
|View full text |Cite
|
Sign up to set email alerts
|

Passive beam forming and spatial diversity in meteor scatter communication systems

Abstract: The method of passive beam formation using a four-element Butler matrix to improve the signal availability of meteor scatter communication systems is investigated. Signal availability, defined as the integrated time that the signal-to-noise ratio (snr) exceeds some sf•r threshold, serves as an important indicator of system performance. Butler matrix signal availability is compared with the performance of a single four-element Yagi reference system using --6.5 hours of data from a 720 km north-south temperate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…A theoretical study by Kilpatrick et al [1991] found that both passive and adaptive systems provide useful increases in throughput. Mawrey and Weitzen [1995] and Akram and Cannon [1996] subsequently confirmed experimentally the advantages cited in favor of the passive method by Kilpatrick et al [1991].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…A theoretical study by Kilpatrick et al [1991] found that both passive and adaptive systems provide useful increases in throughput. Mawrey and Weitzen [1995] and Akram and Cannon [1996] subsequently confirmed experimentally the advantages cited in favor of the passive method by Kilpatrick et al [1991].…”
Section: Introductionsupporting
confidence: 58%
“…Full details about the hardware and the digital signal processing (DSP) implementation of the phased array are given by Akram and Cannon [1996]. It is sufficient to note here that the five phase locked channels of in-phase and quadrature components were logged at ---300 samples/s in data blocks of 500 ms.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond line of sight (BLOS) meteor burst (MB) communications [e.g., McKinley, 1961;Schanker, 1990;Schilling, 1993] via meteor scatter propagation has been studied since the late 1950s, and through this period there has been a steady improvement in system performance [e.g., Cannon and Reed, 1987;Mawrey and Weitzen, 1995;Akram and Cannon, 1996]. One important approach to system improvement has been the propagation experiment which aims to quantify throughput [e.g., Ostergaard et al, 1990] and verify models [e.g., Cannon, 1986].…”
Section: Introductionmentioning
confidence: 99%